Regional ecology : - Dickinson, Robert Eric (Wiley, 1970)
This book seeks to present answers to this question by dealing with the essentials of its expertise in measurement, mapping and interpretation of Man's environment. It does not presume to set limits to the work of any researchers; their efforts will be judged at the bar of scholarship. It does emphatically training at the University level from the undergraduate course to the final doctorate examination.